Neighbourhood systems based attribute reduction in formal decision contexts. Issue 4 (9th December 2019) - Zhang, Xiaohe; Mi, Jusheng; Li, Meizheng; Liang, Meishe
Abstract : Attribute reduction of formal decision context mainly uses the relationship between two concept lattices generated by the condition and decision attributes to remove redundant condition attributes. By using decision attributes to observe the covering of objects, this study defines two types of consistent sets and reducts in a consistent formal decision context based on neighbourhood systems. Four types of reductions in inconsistent formal decision contexts are also studied. The methods to calculate all types of reductions are formulated by discernibility matrix. Finally, an approach to obtain the decision rules in consistent formal decision context is proposed.